Creating critical classrooms : - Lewison, Mitzi (L. Erlbaum Associates, 2008)
This book for elementary and middle school teachers and literacy methods courses articulates a powerful theory of critical literacy instruction. Critical literacy practices encourage students to use language to question the everyday world, interrogate the relationship between language and power, analyze popular culture and media, understand how power relationships are socially constructed, and consider actions that can be taken to promote social justice. By providing both a model for critical literacy instruction and many examples of how critical practices can be enacted in daily school life in elementary and middle school classrooms, Creating Critical Classrooms meets a huge need for a practical, theoretically based text on this topic.